Uma baiana de olhos verdes: Interdisciplinaridade e Estudos Culturais em Carmen Miranda e o Brasil da Colonialidade do poder na década de 1930 - BRUNA RAQUEL NUNES DE MORAIS (2024)
This dissertation explores the coloniality in the Brazilian national identity of the 1930s promoted by the Vargas government and articulated by Carmen Miranda - the greatest interpreter and representative of the national identity of the period, who exalted the nation, samba and the mulatto (a) with her nationalist songs and, in her figure of a whitened mulatto/Bahian. The dissertation aims to debate the coloniality of the 1930s in using mulattos/blacks to compose an identity, stereotyping and sensualizing them, but it is not a work of Ethnic Racial Studies or History, but rather an interdisciplinary work of Cultural Studies. The dissertation was constructed in a decolonial perspective, debating the coloniality in exalting miscegenation/mulatto in a whitened presentation in the figure of Carmen Miranda, who ends up whitening the nation that claimed to be mixed race, but was represented by Carmen's whiteness. The research problem is to highlight and reflect on the coloniality of the national identity of the 1930s in Brazil, which classified races, exalted, stereotyped and sensualized the mulatto in a whitened presentation, redimensioning whiteness. The valorization of miscegenation and the mulatto in the 1930s makes the original lineages of the mestizo/mulatto invisible and becomes a path to hegemonic whiteness. The dissertation is divided into four chapters: chapter one presents the life and career of Carmen Miranda and the mulatto issue of the 1930s in Brazil. Chapter two discusses what coloniality is and how it is present in the Brazilian national identity of the period. Chapter three presents what identity, culture and representation are. And the last chapter analyzes coloniality in the songs recorded by Carmen Miranda, through the discussion of her songs. The research methodology is qualitative, investigating various scientific sources related to Carmen Miranda. In addition to the bibliographical research, an analysis of seven of the artist's songs was carried out. As a result, it is concluded that Carmen Miranda contributed to the legitimization of Brazilian national identity in the 1930s, an identity that updated coloniality by exalting and sensualizing miscegenation/mulatto, by making the subalternized races invisible in miscegenation, by redimensioning whiteness, and by taking samba out of marginality, but not its creators: black people.